2018
DOI: 10.1037/h0101829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flashcards on learning authentic materials: The role of detailed versus conceptual flashcards and individual differences in structure-building ability.

Abstract: Little research has examined the fruitfulness of flashcards for improving learning outcomes of authentic classroom material. In Experiment 1, across different content areas flashcards did not significantly increase performance on a final test relative to the free-study condition. Experiment 2 investigated whether providing conceptual flashcards would aid participants' learning relative to detailed flashcards (the kind generated most frequently by participants). Conceptual flashcards produced superior short-ans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…For this content, instructors might guide students to generate and answer conceptual questions—questions that focus on knowledge about a target concept or require integration across various concepts and principles. Findings show that college learners can successfully pose such questions when instructed to do so (e.g., Bugg and McDaniel, 2012 ; Lin et al. , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…For this content, instructors might guide students to generate and answer conceptual questions—questions that focus on knowledge about a target concept or require integration across various concepts and principles. Findings show that college learners can successfully pose such questions when instructed to do so (e.g., Bugg and McDaniel, 2012 ; Lin et al. , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results involving more complex materials (e.g., anthropology texts; psychology course content) have also been mixed. Lin et al (2018; Experiment 1) found no significant differences between flashcard types as measured on a 20-min delayed test, whereas Cihon et al (2012) reported inconsistent results across two experiments as measured on weekly unit quizzes.…”
Section: Prior Research On Premade Versus User-generated Flashcardsmentioning
confidence: 95%
“…Moreover, there does not appear to be a single design feature that is responsible for the disparate results. For instance, Lin et al (2018) suggested that their study instructions may have been suboptimal, whereas in Cihon et al (2012), only the premade condition studied the exact information to be tested, thus leaving the user-generated condition at a disadvantage.…”
Section: Prior Research On Premade Versus User-generated Flashcardsmentioning
confidence: 99%
“…Do they make flashcards? It takes time to make them and takes extra knowledge to make and use them well (Lin et al, 2018). Of course, retrieval can be as simple as writing down everything one can remember (with or without additional supporting structures, such as concept maps; Blunt & Karpicke, 2014; O'Day & Karpicke, 2021), but our conjecture is that students need practice even with this simple strategy.…”
Section: Lack Of Procedural Metacognitive Knowledgementioning
confidence: 98%